Pharmacologic Therapies to Prevent Relapse of Acute Myeloid Leukemia After Allogeneic Hematopoietic Stem Cell Transplantation - Antar, Ahmad I.; Otrock, Zaher K.; Abou Dalle, Iman; El-Cheikh, Jean; Bazarbachi, Ali (Frontiers in Oncology, 2020)
Relapse is the main cause of mortality in patients with acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Adverse cytogenetic or molecular risk factors, as well as refractory disease or persistent measurable residual disease (MRD) at the time of transplantation are associated with an increased risk of recurrence. Salvage therapy for AML relapse after allo-HSCT is often limited to chemotherapy, donor lymphocyte infusions and/or second transplants and is rarely successful. Effective post-transplant preventive intervention in high risk AML may be crucial. The most frequent and promising approach is the use of post-transplant maintenance with hypomethylating agents or with FLT3 tyrosine kinase inhibitors when the target is present. Moreover, IDH1/IDH2 inhibitors and BCL-2 inhibitors in combination with other strategies are promising approaches in the maintenance setting. Here we summarize the current knowledge about the prophylactic and preemptive use of pharmacologic agents after allo-HSCT to prevent relapse of AML.